PERAN IBU DALAM UPAYA PENCEGAHAN DIARE PADA BALITA DI KELURAHAN KENALI ASAM BAWAH - Tina Yuli Fatmawati (Jurnal Akademika Baiturrahim Jambi, 2017)
Background: In Indonesia, diarrheal diseases are a major cause of death after respiratory tract infection . There are 7 indicators relating to the prevention of diarrhea, : to give the baby exclusive breastfeeding, complementary feeding, using clean water, hand washing, use of latrines, Throw feces properly and immunization. The purpose of this study was to determine the role of mothers in the prevention of diarrhea in infants.Methods: This research method is a descriptive study, which aims to describe the characteristics of the mother, knowledge and PHBS mothers in the prevention of diarrhea in infants, this study was conducted in April-July 2016 in Kenali Asam Bawah, the population of all mothers with toddlers aged 1-5 years totaled 56. Analysis data using univariate.Results: The results obtained from 56 mothers who have children know the highest maternal age between 20-30 years old by 30 (53.6%), with a high school education 36 respondents (64.3), a good knowledge of (80.4%), respondents have PHBS :breastfeeding well at (82.1%), complementary foods well at (82.1%), use of latrines well (55.4%), immunization with both (100%).